1985
DOI: 10.1161/01.res.56.5.755
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propranolol on atherogenesis in the cholesterol-fed rabbit.

Abstract: SUMMARY. These studies have examined the effects of d/-propranolol, d-propranolol, and metoprolol on aortic atherogenesis in the cholesterol-fed rabbit and have correlated the vascular effects of the drugs with their influence on blood pressure, plasma lipids and lipoproteins, arterial metabolism, and arterial permeability. rf/-Propranolol, and, to a lesser extent, d-propranolol, used in clinically relevant doses of 5 mg/kg body weight per day, inhibited the development of aortic atherosclerosis in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…In this study, tissue lipid peroxidation products, both before and after the ischemia-reperfusion episodes, were significantly reduced in the propranololtreated hearts compared with control (Khaper et al, 1997). In an earlier study, Chobanian et al (1985) observed that both D and L forms of propranolol were able to protect against atherosclerosis in cholesterol-fed rabbits, suggesting other nonpharmacological properties of propranolol might be beneficial. Because increased free radical generation was implicated in the pathogenesis of a variety of cardiovascular diseases, including ischemia/reperfusion injury, restenosis, and atherosclerosis (Steinberg et al, 1989;Halliwell and Gutteridge, 1990), we examined the membrane antiperoxidative activities of several ␤-blockers.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In this study, tissue lipid peroxidation products, both before and after the ischemia-reperfusion episodes, were significantly reduced in the propranololtreated hearts compared with control (Khaper et al, 1997). In an earlier study, Chobanian et al (1985) observed that both D and L forms of propranolol were able to protect against atherosclerosis in cholesterol-fed rabbits, suggesting other nonpharmacological properties of propranolol might be beneficial. Because increased free radical generation was implicated in the pathogenesis of a variety of cardiovascular diseases, including ischemia/reperfusion injury, restenosis, and atherosclerosis (Steinberg et al, 1989;Halliwell and Gutteridge, 1990), we examined the membrane antiperoxidative activities of several ␤-blockers.…”
supporting
confidence: 51%
“…2-5), it is feasible that the antioxidant potency of 4HOP may be pharmacologically relevant especially in patients receiving high doses of propranolol. We speculate that the anti-LDL oxidative effect of 4HOP may explain the protective effect of propranolol (both D or L forms) administration against the induced atherosclerosis in the rabbits observed by Chobanian et al (1985). This property may also provide a plausible explanation for the reduced susceptibility of LDL to in vitro Cu 2ϩ -mediated oxidation in those patients with coronary disease on ␤-blocker therapy (Croft et al, 1992;Dimmitt et al, 1998).…”
Section: Discussionmentioning
confidence: 85%
“…The direct correlation between BP and the severity of atherosclerosis that we see when BP is altered by 3 different means, combined with the fact that enalapril did not significantly decrease the BP or lesion size of normotensive NNee animals in our experiments, suggests that at least part of the beneficial effect of enalapril is directly due to decreased BP. Furthermore, other antihypertensive drugs, including β-adrenergic blockers and calcium antagonists that do not act through the renin-angiotensin system, are also antiatherogenic in both humans and cholesterol-fed animal models (6,(38)(39)(40). Testing these drugs on nnee mice will be informative in distinguishing whether the mechanism of NO protection against atherosclerosis is due to its local effects or to its systemic effects on BP.…”
Section: Figurementioning
confidence: 99%
“…Several antihypertensive drugs, particularly j8-blockers 46 ' 47 and calcium antagonists, 4849 have inhibited atherogenesis in normotensive cholesterol-fed animals. The mechanism of effect of any of these agents remains unknown, 50 although an obvious feature common to all of these drugs is their ability to lower blood pressure or alter hemodynamic stresses on the arterial wall.…”
Section: Effects Of Antihypertensive Drugsmentioning
confidence: 99%